PELATIHAN PENELITIAN TINDAKAN KELAS BAGI GURU-GURU SLTP SE KECAMATAN TEPUS DAN TANJUNGSARI GUNUNGKIDUL SEBAGAI UPAYA UNTUK MENINGKA TKAN KEBERHASILAN BELAJAR SISW A - Sudaryanto, Sudaryanto; Suyata, Pujiati; Syamsi, Kastam (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2005)
The purpose of this training in order to conduct service community through the Sibermas Program is to increase skills and knowledge of the teachers of the secondary Tepus and Tanjungsari school in constructing and conducting Classroom Action Research. The participants of this service community are 20 subject matter teachers from any content areas of Tepus and Tanjungsari Secondary School. The training is held from August 27 to 29 2002. The constructing research proposal is conducting in a week between August 30 and September 5, 2002. The monitoring of research activities is held between September 15 and October 30. The training used techniques of lecture, discussion, tutorial, and monitoring. The result if this training’ activity is that all of the teachers followed this activity have competencies of Classroom Action Research including basic consept, procedurs, constructing proposal, implementing, and reporting. There are 13 teachers could construct Classroom Action Research proposal. Two of them funded to conduct of research, those are the group from Tepus 2 Secondary School and Tanjungsari 2 Secondary School. Basid on the result, it could be concluded that this training activity could increase the skills and knowledge of the Secondary School teachers in contructing and conducting Classroom Action Research so this activity that could increase the achievement of he students. Key words: Sibermas, Classroom Action Research